The economic interpenetration between the European Union and Eastern Europe - European Commission. Directorate-General II Economic and Financial Affairs (European economy, ISSN 0379-0991, 1995)
Summary (ix-xiii).
Keywords: itäinen Keski-Eurooppa; Euroopan yhteisöt : kauppapolitiikka; talouselämä : Bulgaria; talouselämä : Puola; talouselämä : Romania; talouselämä : Tšekkoslovakia; talouselämä : Unkari; ulkomaankauppa : Bulgaria; ulkomaankauppa : Puola; ulkomaankauppa : Romania; ulkomaankauppa : Tšekkoslovakia; ulkomaankauppa : Unkari; siirtymätalous